Impact of Various Sedation Methods in Patients with Acute Severe Brain Injury on Lipid Peroxidation - V. V. Unzhakov; S. K. Sukhotin (Общая реаниматология)
Objective: to study the impact of various sedation methods on lipid peroxidation in patients with acute severe brain injury. Subjects and methods. For this, 44 victims with this condition were examined. According the option of posttraumatic sedation therapy, the victims were divided into 3 groups: 1) 12 patients in whom sodium oxybutyrate was used for sedation; 2) 12 received thiopental sodium; 3) 20 patients were given propofol. The lipid peroxidation and antioxidant system were judged from the serum levels of fatty acid hydroperoxides and secondary lipid peroxidation products (malonic dialdehyde) and from the content of the endogenous antioxidant a-tocopherol. Results. The study performed indicated that the highest concentrations of fatty acid hydroperoxides were observed in Groups 1 and 2 within the first 24 posttraumatic hours. In Group 3 where propofol was used for sedation, the concentration of the hydroperoxides remained in the normal range although there was a tendency for their rise. Conclusion. Thus, propofol is the agent of choice for sedation that prevents the activation of lipid peroxidation and stabilizes some indices of the antioxidant system in patients with acute severe brain injury. Key words: brain injury, lipid peroxidation, sedation, sodium oxybutyrate, thiopental sodium, propofol.